PENYUSUNAN SOP KAWASAN WISATA DUSUN SEGUNUNG, DESA CARANG WULUNG KECAMATAN WONOSALAM, KABUPATEN JOMBANG - Ulfi Pristiana; Nanis Susanti (Gapenas Publisher, 2021)
The application of SOPs in service to the community needs to be considered between the organizational structure and the division of tasks within the government and is associated with several important things in the implementation of SOPs which include efficiency, consistency, error minimization, problem solving, protection of workers (employees), work maps and defense boundaries. Segunung Hamlet, Carangwulung Village, Wonosalam District, Jombang Regency. It is a tourism hamlet that has been running for 1.5 years and has been visited by many tourists, but in all the activities carried out it does not yet have an SOP about tourist villages in Segunung hamlet, Wonosalam, Jombang Regency.” The implementation of the service activities that have been carried out has resulted in a conclusion that the Segunung Indigenous Tourism Hamlet is a tourist area that has the opportunity to be developed, Good governance has been carried out, even though it is in improvised conditions and it is necessary to set a standard operating procedure that can be used as a standard in the development and implementation of activities for the creation of a Tourism Village that provides education to the community. Therefore, it is necessary to provide additional knowledge for the residents through increasing knowledge in each group which is divided into existing fields and sub-fields. In addition, better supporting facilities are needed, including developing infrastructure such as educational parks, bathrooms or toilets for visitors